"It seems impossible that it's been made so quickly": a qualitative investigation of concerns about the speed of COVID-19 vaccine development and how these may be overcome. Issue 1 (31st December 2022) - Brown, Poppy; Waite, Felicity; Larkin, Michael; Lambe, Sinéad; McShane, Helen; Pollard, Andrew J.; Freeman, Daniel
ABSTRACT: The speed of COVID-19 vaccine development has been identified as a central concern contributing to hesitancy in acceptance. We conducted qualitative interviews to gain a greater understanding into these concerns and to identify what might address them. Twelve qualitative interviews were conducted with participants identifying as hesitant for COVID-19 vaccination and reporting concern about the speed of vaccine development. Interpretative Phenomenological Analysis (IPA) was used. Concerns about speed comprised the linked themes of i) difficulty understanding the pace, and, ii) worry about the implications for vaccine safety. Uncertainties concerning the pandemic led to a notable desire for credible and understandable information regarding the vaccines, which many participants felt was not available. Four routes to resolving uncertainty about whether to be vaccinated were identified. First, waiting for more information about the vaccines, such as about their contents and impact on transmission. Second, a growing perception that the vaccines must be safe given the large numbers already vaccinated. Third, viewing the vaccines as necessary – even if unappealing – for ending the pandemic. Finally, a feeling that there would be no choice but to have a vaccine. Examples of what might reduce hesitancy were given, including interviews with vaccine developers and knowing others of similar age having safely been vaccinated. The pace of development broke expectations set earlier in the pandemic. This was interpreted negatively due to a perceived lack of credible information. Most participants could envisage ways their concerns could be resolved, enough for them to have a vaccine.